Design of topological terahertz quantum cascade laser - Eng, John Jun Hong (Nanyang Technological University, 2021)
Arising from condensed matter physics, topological photonics grants a new degree of freedom to design photonic devices with modes robust against perturbations arising from fabrication and sharp corners. For semiconductor laser systems, namely quantum cascade laser (QCL), it allows for non-conventional cavity designs and perhaps interesting lasing properties through one of the many topological phases. One such effect is the quantum spin Hall effect (QSHE) which requires pseudospin-orbital coupling. Here, we propose a laser cavity design that could mimic the QSHE to produce light with spin angular momentum (SAM) while having the benefits of topologically protected modes.